Asesmen Formatif Pada PAUD Di Indonesia - Agung Prihantoro (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2021)
Formative assessment in early childhood education in Indonesia does not have been working well. The research aims to prove the problem that the formative assessment (assessment for learning and assessment as learning) in early childhood education in Indonesia does not have been performing well. The research employed the research methodology of literature review to investigate the problem by analyzing empirical research-based articles on assessment in early childhood education. The result shows that a very few of natures of the formative assessment were present when teachers of early childhood education assessed their students. Goals, teacher’s and student’s roles, methods, feedback and following actions which particularly characterize the formative assessment were seldom found in the assessment practice in early childhood education in Indonesia.